Asia, Europe, and the Emergence of Modern Science
IX, 282 p.
Keywords: This volume brings together essays from leading thinkers to examine what role Asian traditions of knowledge played in the rise of modern science in Europe, the implications this has for the epistemology of science, and whether pre-modern Asian traditions can provide resources for advancing scientific knowledge in future.